Experiences and perspectives of community health workers from implementing treatment for schistosomiasis using the community directed intervention strategy in an informal settlement in Kisumu City, western Kenya - Gladys O. Odhiambo; Rosemary M. Musuva; Maurice R. Odiere; Pauline N. Mwinzi (BMC, 2016)
Abstract Background The Community Directed Intervention (CDI) strategy has been used to conduct various health interventions in Africa, including control of Neglected Tropical Diseases (NTDs). Although the CDI approach has shown good results in the control of onchocerciasis and lymphatic filariasis with respect to treatment coverage using community drug distributors, its utility in the control of schistosomiasis among urban poor is yet to be established. Using a longitudinal qualitative study, we explored the experiences, opportunities, challenges as well as recommendations of Community Health Workers (CHWs) after participation in annual mass drug administration (MDA) activities for schistosomiasis using the CDI approach in an urban setting. Methods Unstructured open-ended group discussions were conducted with CHWs after completion of annual MDA activities. Narratives were obtained from CHWs using a digital audio recorder during the group discussions, transcribed verbatim and translated into English where applicable. Thematic decomposition of data was done using ATLAS.ti. software, and themes explored using the principle of interpretative phenomenological analysis (IPA). Results From the perspective of the CHWs, opportunities for implementing CDI in urban settings, included the presence of CHWs, their supervisory structures and their knowledge of intervention areas, and opportunity to integrate MDA with other health interventions. Several challenges were mentioned with regards to implementing MDA using the CDI strategy among them lack of incentives, fear of side effects, misconceptions regarding treatment and mistrust, difficulties working in unsanitary environmental conditions, insecurity, and insufficient time. A key recommendation in promoting more effective MDA using the CDI approach was allocation of more time to the exercise. Conclusion Findings from this study support the feasibility of using CDI for implementing MDA for schistosomiasis in informal settlements of urban areas. Extensive community sensitization and provision of incentives may help address the aforementioned challenges associated with implementing MDA using the CDI strategy. Opportunities highlighted in this study may be of value to other programmes that may be considering the adoption of the CDI strategy for rolling out interventions in the urban setting.